Middle Powers and the Rise of China - BRUCE GILLEY, ANDREW O’NEIL (Georgetown University Press, 2014)
THIS BOOK was conceived over a series of conversations about the significance of middle power interactions with China and what these tell us about the nature of China’s rise in international relations. This culminated in a two-day workshop in Brisbane in July 2012, funded by Griffith University’s Program of Asian Politics, Security and Development.